1980
DOI: 10.1051/rnd:19801013
|View full text |Cite
|
Sign up to set email alerts
|

Transport of spermatozoa in the ewe : timing of the establishment of a functional population in the oviduct

Abstract: Summary. The technique of post-coital transection of the oviducts from the uterus at various intervals after mating has been used to establish how soon a population of spermatozoa competent to fertilise the egg(s) first appears in the oviduct of the ewe. Fertilised eggs were not found as a sequel to transection at 4 or 6 hrs after mating, whereas the incidence of fertilisation irt a small series of ewes was 30 p. 100 following transection at 8 hrs and 100 p. 100 at 10 hrs. The mean number of spermatozoa associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
31
0
1

Year Published

1983
1983
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(33 citation statements)
references
References 19 publications
1
31
0
1
Order By: Relevance
“…Following preliminary observations in rabbits (Harper, 1973a,b) and bats (Racey et al, 1975;Racey, 1979) and detailed surgical studies in sheep (Hunter et al, 1980Nichol, 1983, 1986), pigs (Hunter, 1981(Hunter, , 1984 and cows Wilmut, 1982, 1984;Wilmut and Hunter, 1984), the caudaldistal-portion of the oviduct isthmus was recognised as a significant pre-ovulatory reservoir for viable spermatozoa, even though substantial sperm populations might still be found in lower regions of the tract. The term functional sperm reservoir was therefore proposed for the caudal isthmus since it represents the region from which fertilising spermatozoa are released close to the time of ovulation (Hunter et al, 1980;Hunter, 1981).…”
Section: Functional Sperm Reservoirmentioning
confidence: 99%
See 1 more Smart Citation
“…Following preliminary observations in rabbits (Harper, 1973a,b) and bats (Racey et al, 1975;Racey, 1979) and detailed surgical studies in sheep (Hunter et al, 1980Nichol, 1983, 1986), pigs (Hunter, 1981(Hunter, , 1984 and cows Wilmut, 1982, 1984;Wilmut and Hunter, 1984), the caudaldistal-portion of the oviduct isthmus was recognised as a significant pre-ovulatory reservoir for viable spermatozoa, even though substantial sperm populations might still be found in lower regions of the tract. The term functional sperm reservoir was therefore proposed for the caudal isthmus since it represents the region from which fertilising spermatozoa are released close to the time of ovulation (Hunter et al, 1980;Hunter, 1981).…”
Section: Functional Sperm Reservoirmentioning
confidence: 99%
“…The term functional sperm reservoir was therefore proposed for the caudal isthmus since it represents the region from which fertilising spermatozoa are released close to the time of ovulation (Hunter et al, 1980;Hunter, 1981). Scanning electron microscopy of oviduct tissues removed at surgery and subjected to gentle rinsing before fixation suggested some form of adhesion between the sperm head and protruding epithelial organelles of the caudal isthmus, either cilia or microvilli or both (Fléchon and Hunter, 1981;Hunter et al, 1987Hunter et al, , 1991, a conclusion also reached by Yanagimachi (1990, 1991), Pollard et al (1991), Suarez et al (1991) and Mburu et al (1997).…”
Section: Functional Sperm Reservoirmentioning
confidence: 99%
“…Du Mesnil du Buisson and Dauzier [5] had suspected that either the utero-tubal junction or the isthmus might act as a sperm reservoir, and by surgical and histological studies the latter was shown to be true in pigs [6], sheep [7] and cows [8,9]. We termed the caudal portion of the isthmus the functional sperm reservoir [10], for it was from this region of the tract that spermatozoa involved in the events of fertilisation were activated and released close to the time of ovulation.…”
Section: Functional Sperm Reservoirmentioning
confidence: 99%
“…Fur-thermore, insemination at an inappropriate time relative to ovulation is known to reduce fertility (Trimberger, 1948 ;Deas, 1970 ;MacMillan and Watson, 1975a, b ;Robbins et al, 1978 ;Foote, 1979), partly because the proportion of eggs fertilised is reduced, but also because those eggs fertilised after a postovulatory delay are more likely to die during embryonic development (Casida, 1950 (Hunter, 1984). Previous studies in this species have used counts of spermatozoa in flushings (VanDemark and Moeller, 19511, smears (Dauzier, 1958) and histological preparations (Thibault, G6rard and Heyman, 1973) (Dauzier, 1958 ;Thibault et al, 1973 which species no eggs were fertilised after ligation at 4 or 6 hr, but 30 % and 100 % were fertilised following section 8 and 10 hr after mating, respectively (Hunter, Nichol and Crabtree, 1980). These results suggests that in cattle the process of establishing the functional population in the oviduct had begun by 6 hr after mating, but was incomplete even a further 6 hr later.…”
Section: Introductionmentioning
confidence: 99%